A Critical Review on Improving the Productivity of Microalgae Cultivated in Wastewater for Biofuel Production (International Journal of Innovative Research in Computer Science & Technology, 2020)
Microalgae has been recognized as a  possible feedstock for the assembling of biofuels. On  account of their natural nonpartisanship and adaptability  underway, microalgae have arisen as a potential feasible  biomass asset. Joining microalgae cultivation with  wastewater treatment successfully lessens CO2 discharges  and brings down the expense of delivering microalgae  biofuel, making it more feasible. Preceding enormous  scope creation, nonetheless, biomass and lipid efficiency  should be expanded. Thus, the survey gives a basic  appraisal of microalgae's usefulness for biofuel age,  focusing on the influencing factors, for example, strains  and culture conditions. In light of this review, we propose  using a combination of nearby green growth species and a  two-stage culture technique to accomplish an economical  and practical microalgae biofuel creation involving  wastewater as a medium. Despite its prospects as a biofuel  feedstock, green growth's commitment to biofuel creation  is restricted because of its significant expense and huge  asset utilization.
Keywords: Cultivation Strategy; Lipid; Microalgae; Mixed-Native Algae